ANALISIS TINGKAT KESEHATAN PERBANKAN MENGGUNAKAN METODE RISK-BASED PADA PT.BANK MUAMALAT INDONESIA - Sari, Ratna Kurnia; Wati, Fanny Fatma; Widodo, Andrian Eko; Abidin, Muhammad Ali Zaenal (LPPM UBSI Kampus Kota Tegal, 2022)
Banking is a financial institution that has great potential and enormous social value to grow and develop in carrying out its role as a source of financing for customers and the business sector, especially in facing the era of globalization in a country, especially Indonesia. Likewise, the soundness of a bank becomes a barometer of the ability to compete in the business world, because a bank is a company. Therefore, it is very important to maintain public trust in its performance. Based on Bank Indonesia regulation, bank soundness assessment will be very useful in implementing Good Corporate Governance and for dealing with future risks. The Risk-Based Bank Rating method is a policy issued by the government as a tool for assessing the soundness of a bank with the scope of the assessment covering the following factors: Risk profile, Good Corporate Governance , Profitability and Capital to produce a composite rating of bank soundness. The purpose of this study was to determine the soundness of the bank on the balance sheet items, profit and loss and cash flow as well as the financial performance of PT. Bank Muamalat Indonesia Tbk uses the Risk-Based Bank Rating method for 3 years. The results of the research generally show that PT Bank Muamalat Indonesia Tbk is in the composite rank 3 with the criteria of